2010
DOI: 10.1111/j.1471-4159.2010.06824.x
|View full text |Cite
|
Sign up to set email alerts
|

Actin interaction and regulation of cyclin-dependent kinase 5/p35 complex activity

Abstract: J. Neurochem. (2011) 116, 192–204. Abstract Cyclin‐dependent kinase 5 (Cdk5) plays a critical role during neurodevelopment, synaptic plasticity, and neurodegeneration. Cdk5 activity depends on association with neuronal proteins p35 and p25, a proteolytic product of p35. Cdk5 regulates the actin cytoskeletal dynamics that are essential for neuronal migration, neuritic growth, and synaptogenesis. However, little is known about the interaction of actin and Cdk5 and its effect on neuronal Cdk5 activity. In a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Primary neural stem cell cultures were prepared from mouse embryonic brain at embryonic day 14 as previously described (29,71). Briefly, cells were cultured as neurospheres for 7 d until spheres reached 100 to 150 μm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…Primary neural stem cell cultures were prepared from mouse embryonic brain at embryonic day 14 as previously described (29,71). Briefly, cells were cultured as neurospheres for 7 d until spheres reached 100 to 150 μm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…Seven days after infection, cells were fixed with 4% paraformaldehyde (PFA, Sigma-Aldrich) and immunocytochemistry was conducted as reported (44). Briefly, in order to visualize plasma membrane-localized NEP, fixed cells were not permeabilized prior to incubation with blocking buffer containing 5% BSA and 5% normal donkey serum in PBS for 1 hour at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that TTBK1 activates Cdk5 via dissociation of Cdk5 from G-actin and recruitment of p35/ p25 to Cdk5 [7,40]. Other evidence has shown that Cdk5 directly phosphorylates CRMP2 at Ser522, which is the priming step of the phosphorylation of CRMP2 at threonine 514 (T514) by GSK3β and this phosphorylation of CRMP2 at T514 is critical for the induction of neurite retraction [13].…”
Section: Ttbk1 Expression and Aβ Stimulation Induces Crmp2 Phosphorylmentioning
confidence: 99%